Activation of phosphatidylinositol 3-kinase by epidermal growth factor, basic fibroblast growth factor, and nerve growth factor in PC12 pheochromocytoma cells. - Raffioni, S (1992)
Epidermal growth factor (EGF), basic fibroblast growth factor (bFGF), and nerve growth factor (NGF), which stimulate the phosphorylation of proteins on tyrosine in PC12 cells, initiate these modifications through ligand-specific cell surface receptors that contain the causative tyrosine kinases. One apparent substrate for these enzymes is phosphatidylinositol 3-kinase (PI 3-kinase), an enzyme that phosphorylates the D-3 position of the inositol ring and associates with several protein tyrosine kinases, as indicated by the fact that it is immunoprecipitated from EGF-, bFGF-, and NGF-stimulated PC12 cells by an anti-phosphotyrosine antibody. All three growth factors increase immunoprecipitable PI 3-kinase activity after 2 min of addition at concentrations able to stimulate either mitogenic or neurotrophic responses in PC12 cells. The level of stimulation of PI 3-kinase activity by EGF, bFGF, and NGF is 15- to 20-fold, 2- to 3-fold, and 8- to 10-fold, respectively. Moreover, tyrosine phosphorylation of PI 3-kinase was detected in EGF-, bFGF-, and NGF-stimulated PC12 cells, and the amount of the phosphorylation correlated with the level of stimulation of enzyme activity. In contrast, phosphatidylinositol 4-kinase, which produces the inositol phospholipids cleaved by phospholipase C-gamma to yield diacylglycerol and inositol-1,4,5-trisphosphate, is not affected by these growth factors. The pattern of stimulation of PI 3-kinase does not correlate with the induction of neurite outgrowth but rather with the mitotic responses, suggesting that PI 3-kinase and its products may be more important for signaling in cell division than in trophic processes. However, the levels of phosphatidylinositol 3-phosphate do not coincide with the stimulation of [3H]thymidine incorporation by these growth factors, rendering its role in mitotic functions, at least in PC12 cells, also uncertain.